Need for Affiliation as a Motivational Add-On for Leadership Behaviors and Managerial Success - Steinmann, Barbara; Ötting, Sonja K.; Maier, Günter W. (Frontiers in Psychology, 2016)
In a sample of 70 leader-follower dyads, this study examines the separate and interactive effects of the leaders’ implicit needs for power, achievement, and affiliation on leadership behaviors and outcomes. Results show that whereas the need for achievement was marginally associated with follower-rated passive leadership, the need for affiliation was significantly related to ratings of the leaders’ concern for the needs of their followers. Analyzing motive combinations in terms of interactive effects and accounting for the growing evidence on the value of affiliative concerns in leadership, we assumed the need for affiliation would channel the interplay among the needs for power and achievement in such a way that the leaders would become more effective in leading others. As expected, based on high need for achievement, the followers were more satisfied with their jobs and with their leaders and perceived more transformational leadership behavior if power-motivated leaders equally had a high need for affiliation. Moreover, the leaders indicated higher career success when this was the case. However, in indicators of followers’ performance, the three-way interaction among the needs for power, achievement, and affiliation did not account for additional variance.